HONESTY IS A HIGH SPIRITUAL-MORAL VIRTUE - Kulmatov, Primkul Meliko‘zievich; Mamanov, O. (Educational Research in Universal Sciences, 2024)
This article talks about honesty and duty, which are one of the most beautiful qualities in a person, and about its place and role in the life of society.